The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/prot.22157
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of the loop‐to‐helix transition leading to the coiled‐coil structure of influenza virus hemagglutinin HA2 subunits

Abstract: Fusion of influenza virus with the endosomal membrane of the host cell is mediated by the homotrimer-organized glycoprotein hemagglutinin (HA). Its fusion activity is triggered by a low pH-mediated conformational change affecting the structure of the HA1 and HA2 subunits. The HA2 subunits undergo a loop-to-helix transition leading to a coiled-coil structure, a highly conserved motif for many fusion mediating viral proteins. However, experimental studies showed that the HA2 coiled-coil structure is stable at ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 70 publications
(54 reference statements)
2
17
0
Order By: Relevance
“…In order to drive the loop-to-helix transition and the formation of a coiled-coil structure, it is necessary for water molecules to directly interact with the hydrophilic residues 15 . Therefore, the ability of INT to stabilize the connection between HA1 and HA2 and to effectively prevent water from entering into the interior of HA2 is crucial for the inhibitory activity of INT.…”
Section: Resultsmentioning
confidence: 99%
“…In order to drive the loop-to-helix transition and the formation of a coiled-coil structure, it is necessary for water molecules to directly interact with the hydrophilic residues 15 . Therefore, the ability of INT to stabilize the connection between HA1 and HA2 and to effectively prevent water from entering into the interior of HA2 is crucial for the inhibitory activity of INT.…”
Section: Resultsmentioning
confidence: 99%
“…Both of these studies have indicated the S-helix to be parallel CC and modeled it as such. Some possible CC conformational changes could involve a loop-to-helix transition, as observed in influenza virus hemagglutinin HA2 [45], a shifting/flipping along the interface of the a-d knobs, as modeled for GCN4 [46], or rotation of the helices as evidenced in the HAMP structure [31]. In addition, a helix re-orientation from anti-parallel to parallel or vice versa can also not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…In most influenza strains, this HisCat cluster is surrounded by additional cations; a His is highly conserved at position 185 and other cations often cluster around this region (Figure 5A). Indeed, this HisCat cluster lies at the HA1/HA1 interface and molecular dynamics simulations have predicted that as the pH decreases the HA1/HA1 interface is destabilized, opening a channel for water to solvate HA2 (Huang et al, 2002, 2009; Korte et al, 2007). …”
Section: Influenza a Virus Ha1/ha2mentioning
confidence: 99%